Dark side behavior and satisfaction in business relationships between companies. Literature review - Ayala-Regalado, Carlos Javier (2022)
Business relationships are essential in relationship marketing since their proper management allows companies to obtain benefits. Different factors can affect these relationships, among which dark side behaviors can be counted. These behaviors include concealing information, opportunism, generating confusion, data sale, deception, disrespect for privacy, and unjustified charges. This study identifies research focused on dark side behaviors and their relationship with satisfaction in business relationships between companies. We systematically reviewed the literature produced between 2010 and 2022 and identified theories, authors, methodologies, limitations of the studies and opportunities for future research.